2012
DOI: 10.1111/j.1475-3588.2012.00667.x
|View full text |Cite
|
Sign up to set email alerts
|

Parent experiences of a specialist intervention service for mental health difficulties in children with autistic spectrum disorder

Abstract: Background Mental health problems are increasingly being recognised as a significant health need for people with autism spectrum disorder, but few specialist services are available. This study explored parents’ experiences of a specialist autism spectrum psychological intervention service located within a broader Neurodevelopmental and Social Communication Disorders Team. Method Forty‐nine parents completed a telephone based survey designed to assess experiences of a specialist intervention service. Results Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Although this belief may act as a buffer for parents to cope, it is important to note that there is no cure for autism. 12 These beliefs should not be left alone as it may lead to false hopes or a continuous denial of the diagnosis, possibly leading to maladaptation to the disorder and impairment in the family’s quality of life. Thus relevant health care professionals such as counselors need to ensure that parents are aware of this fact and help them overcome the psychological impact of the diagnosis while guiding them toward acceptance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this belief may act as a buffer for parents to cope, it is important to note that there is no cure for autism. 12 These beliefs should not be left alone as it may lead to false hopes or a continuous denial of the diagnosis, possibly leading to maladaptation to the disorder and impairment in the family’s quality of life. Thus relevant health care professionals such as counselors need to ensure that parents are aware of this fact and help them overcome the psychological impact of the diagnosis while guiding them toward acceptance.…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 11 Other core symptoms involve the lack of or poor language skills and repetitive speech. 9 ASD has no cure and is lifelong; 12 thus, currently available treatments are not directed for cure but are aimed at improving the overall functioning of the child with autism. 13 …”
Section: Introductionmentioning
confidence: 99%
“…The course, symptom severity, and behaviors can vary widely among individuals with ASD (Chang, Lung, Yen, & Yang, 2013). Services children with ASD may benefit from include supports for adaptive behavioral needs (Konst, Matson, Goldin, & Rieske, 2014), including social and communication skills (National Research Council, 2001) as well as for hyperactivity and inattention (Kingston, Hibberd, & Ozsivadjian, 2013; Konst et al, 2014; Ozonoff & Rogers, 2003). …”
mentioning
confidence: 99%
“…The child’s disruptive behaviour is often attributed to the parents’ poor child rearing abilities, leaving them with feelings of being disrespected by health professionals when voicing their concerns. In a study conducted by Kingston, Hibberd, & Ozsivadjian, (2013) parents identified the need for improved access to the health service with increased support for children being hospitalised with autism spectrum disorder, and preferably with less of an institutionalised environment.…”
Section: Discussionmentioning
confidence: 99%